1982
DOI: 10.1111/j.1744-7348.1982.tb01940.x
|View full text |Cite
|
Sign up to set email alerts
|

Chemical suppression of the sexual stage of Leptosphaeria maculans on oil‐seed rape and turnip seed crop straw

Abstract: A selection of fungicides, herbicides and surfactants and urea were tested for their effect on the production of pseudothecia and ascospore release of Leptosphaeria maculans present on oil-seed rape straw and turnip seed crop straw. The fungicides ethyl mercury phosphate, triarimol, fenarimol, carbendazim, tridemorph and benomyl, each at 1 g/litre, the herbicides dinoseb and diquat, each at 10 g/litre the surfactants Bradasol, Cetrimide, Deciquam 222, Hyamine 1622 and Maxonol N, each at 50 g product/litre, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

1984
1984
2013
2013

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 11 publications
0
7
0
1
Order By: Relevance
“…Stubble treatment with triadimefon did not affect canker and none of the stubble treatments decreased ascospore release from stubble pieces. Unlike Humpherson- Jones & Burchill (1982) we found no evidence to suggest that it may be possible to break the life cycle of L. maculans by chemical treatment, although in their experiments straw pieces were dipped in solutions of test chemicals. Our results indicate that in all experiments where fungicides were effective and long lasting they acted systemically to delay or prevent the formation of new lesions.…”
Section: Control Of Light Leaf Spot On Rape 625mentioning
confidence: 58%
“…Stubble treatment with triadimefon did not affect canker and none of the stubble treatments decreased ascospore release from stubble pieces. Unlike Humpherson- Jones & Burchill (1982) we found no evidence to suggest that it may be possible to break the life cycle of L. maculans by chemical treatment, although in their experiments straw pieces were dipped in solutions of test chemicals. Our results indicate that in all experiments where fungicides were effective and long lasting they acted systemically to delay or prevent the formation of new lesions.…”
Section: Control Of Light Leaf Spot On Rape 625mentioning
confidence: 58%
“…and the disease severity within the crop (McGee & Emmett, 1977; Petrie, 1994, 1995c; Turkington et al ., 2000a; Marcroft et al ., 2003). Other studies have shown that ascospore discharge can be reduced by the direct application of chemicals on canola stubble (Humpherson‐Jones & Burchill, 1982; Petrie, 1995b; Turkington et al ., 2000b; Wherret et al ., 2003). However, a commercial method for exploiting chemical applications has not yet been developed.…”
Section: Discussionmentioning
confidence: 99%
“…Humpherson-Jones and Burchill (1982) reported that several fungicides applied to rapeseed residues before pseudothecia had developed were effective in preventing further development; furthermore, ascospore production was suppressed when some fungicides were applied to residues bearing mature pseudothecia. However, Rawlinson et al (1984) found no effect of fungicides applied to rapeseed residues.…”
Section: Controlmentioning
confidence: 98%